Alat Sterilisasi Lampu UVC Portable Berbasis IOT - Qoriatul Fitriyah; Yeni Delfiana Siahaan; Muhammad Prihadi Eko Wahyudi (Politeknik Negeri Batam, 2022)
This research was conducted to increase the reliability of UVC lamp irradiation in killing viruses. Since it was first discovered in November 2019, the COVID-19 pandemic has spread all around us and claimed many lives. Various precautions have been taken by the government and individuals. One of the preventions that can be done is to sterilize the room or object surface by using UV light. To kill the virus, type C ultraviolet (UV) light can be used. With a dose of 220J/m² it produces a reduction in the SARS-CoV-2 or covid-19 virus in the air or a surface. The problem that arises is, the UVC lamp used is only limited to on-off with an erratic duration. This tool is expected to be able to perform calculations automatically to determine the duration of the irradiation just by entering the room area information. For user safety when using UVC rays, this tool will also be equipped with a remote control and presence sensor.